ISPC Commentary on the Revised Proposal for CRP3.3 - September 2010 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2010)
Interim Independent Science and Partnership Council Commentary on CRP 3.3: GRiSP, Global Rice Science Partnership (Revision of September 2010).